Pancreatic Cancer: Current Concepts, Trends, and Future Directions - Wenzel, Patrick; Mogler, Carolin; Görgülü, Kıvanç; Algül, Hana (Turkish Journal of Gastroenterology, 2025)
Pancreatic ductal adenocarcinoma (PC) ranks among the deadliest cancers, with a less than 15% 5-year survival rate. Epidemiological studies project that it will become the second leading cause of cancer-associated mortalities in the following decades. The hallmarks of pancreatic cancer lead to tumor aggressiveness and therapeutic resistance. For this reason, the field has been focusing on multiple dimensions to generate better therapeutic approaches, including new adjuvant, neoadjuvant, and palliative concepts to extend the survival of PC patients. Over the last 2 decades, clinical trials have significantly improved disease prognosis and patient survival. To achieve better outcomes and to deeply understand the therapeutic approaches, molecular tumor boards have become crucial for deeper exploitation of tumor genetics and tumor biology, providing better stratification markers for therapeutic regimens. Using recently developed targeted therapies, such as KRAS inhibitors, the field has gathered momentum and been tooled up with the help of new sequencing technologies. Therefore, researchers and clinicians have geared up for the battle against PC. This review will systematically discuss recent developments in adjuvant, neoadjuvant, and palliative treatment modalities. Moreover, the paradigm-shifting importance of genetic profiling on pancreatic cancer. will be explained through a showcase to frame future directions. Cite this article as: Wenzel P, Mogler C, Görgülü K, Algül H. Pancreatic cancer: current concepts, trends, and future directions. Turk J Gastroenterol. 2025;36(2):69-81.